The lift induced on a circular cylinder by a narrow jet emerging at an angle to the uniform stream - Anderson, R. G. (College of Aeronautics, 1955)
SUMMARY A preliminary qualitative study has been made in a smoke tunnel of the flow around a stationary circular cylinder, having rear jet blowing, placed in a uniform stream. Motographs have been taken which show many interesting flow phenomena. A knowledge of these it is hoped will aid future quantitative studies, It is found that when the jet is deflected downwards at an angle to the mainstream direction boundary layer separation is delayed around the cylinder and the cylinder develops a lift force in addition to its drag. The delay in boundary layer separation is suggested to be mainly the result of the 'sink effect' of the jet mixing. The lift, on :the other hand, appears to be primarily the result of partial attainment of stagnation pressure on both sides of the jet at exit, and is therefore of similar origin to the ‘Thwaites’ flap. A smaller, but no less significant, contribution to the lift arises from the direct and in91rect effects of the jet blowing.